2015
DOI: 10.1590/1807-1929/agriambi.v19n7p698-704
|View full text |Cite
|
Sign up to set email alerts
|

Indução de ivermectina na hormese sobre Eisenia foetida durante a vermicompostagem de esterco bovino

Abstract: R E S U M OOs medicamentos veterinários são, em sua maioria, excretados nas fezes de animais tratados demonstrando que os fármacos da classe das avermectinas podem ter efeitos nocivos sobre os organismos não alvo, caso se utilizem das fezes. O objetivo deste estudo foi determinar os efeitos subletais da ivermectina sobre as minhocas Eisenia foetida expostas às concentrações de ivermectina a 0, 1, 5, 10, 50 e 100 mg kg -1 ; amostras foram tomadas nos dias 7, 14 e 28 de exposição para determinação da sobrevivênc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…In this sense, a set of biochemical alterations can be triggered when specimens of E. foetida are exposed to different concentrations of a toxic substance without compromising their survival (Saint-Denis et al 2001). Moreover, Tuerlinckx et al (2015) have revealed the induction of the hormetic effect by IVM manifested in the rate of development and in the activity of the enzyme alkaline phosphatase in that species.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, a set of biochemical alterations can be triggered when specimens of E. foetida are exposed to different concentrations of a toxic substance without compromising their survival (Saint-Denis et al 2001). Moreover, Tuerlinckx et al (2015) have revealed the induction of the hormetic effect by IVM manifested in the rate of development and in the activity of the enzyme alkaline phosphatase in that species.…”
Section: Discussionmentioning
confidence: 99%